Catholic power in the Netherlands - Bakvis, Herman, 1948- (McGill-Queen's University Press, 1981)
Dutch Catholics long constituted by far the most cohesive political subculture in Western Europe. For nearly half a century virtually all Catholics in the Netherlands supported a single political party - the Catholic party - resisting appeals from both the left and the right. Then in the mid-1960s their allegiance began to crumble; by 1972 only a small minority of Dutch Catholics still voted for the party and a few years later it had ceased to exist.